Students Collaboration in Developing English Learning E-Module Assisted by Canva - Ida Lisdawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
E-module is needed in the learning process because it can support the learning process to run effectively. Based on the observation conducted by the researchers at three junior high schools in Bandung Barat, textbooks used in learning did not support students to understand the material, so the researchers plan to develop an e-module to help teachers and students in English learning. The purpose of this research is to identify the process of developing an e-module, investigate the feasibility of developing an e-module, find out students’ and teacher’s responses, and investigate the challenges in developing an e-module, but this research focuses on getting the validation result as the primary research. The researchers used the research and development (R&D) method by Borg & Gall and Sugiyono's (2014) model. To get the validation result, the researchers used a validation sheet for collecting the data. Validators in this study were two supervisors and one English teacher. Based on the results of validation, the average value obtained was 80%. It was included in the category of feasible and very interesting with excellent information. It could be concluded that the e-module was feasible, excellent, and practical for English learning. It is in line with the research conducted by Arianti & Zainul (2020). They obtain that e-module included in the category of valid and practical. In learning English, the researcher suggests students and teachers use an e-module because it presents an attractive appearance and suits the need of students. In addition, the researcher hopes this research can be used as a reference for other researchers in conducting the next research.